Feasibility of a randomised controlled trial to evaluate home-based virtual reality therapy in children with cerebral palsy. Issue 1 (2nd January 2021) - Farr, William J.; Green, Dido; Bremner, Stephen; Male, Ian; Gage, Heather; Bailey, Sarah; Speller, Sandra; Colville, Valerie; Jackson, Mandy; Memon, Anjum; Morris, Christopher
Abstract: Purpose: Evidence is increasing for effective virtual reality therapy for motor rehabilitation for children with Cerebral Palsy. We assessed the feasibility of a virtual reality therapy mode of intervention, appropriateness of measures, and potential cost-effectiveness. Methods: A 12-week, 2-group, parallel-feasibility trial (ISRCT 17624388) using Nintendo Wii Fit TM at home. Children aged 5–16, with ambulatory Cerebral Palsy, who were able to follow simple instructions were randomised to two groups; one supported by physiotherapists (individualised activity programme), the other unsupported with children having free choice (control). Children were assessed in clinic at baseline, week 6, and week 12 by blinded assessors. Feasibility of the intervention was assessed via recruitment, adherence, and usefulness of measurement tools. Results: Forty-four children were eligible (out of 48 approached): 31 consented, 30 were randomised, 21 completed the study; 10 in the supported group and 11 in the unsupported group. Nine children discontinued from tiredness, after-school activities, homework, surgery, technical difficulties or negative system feedback. The supported group completed 19 of 36 (IQR 5-35) possible sessions; the unsupported group 24 of 36 sessions (IQR 8-36). Gross Motor Function Measure scores varied by Cerebral Palsy severity after the intervention. There were no adverse events. Conclusion: Virtual reality therapy offers potential as a therapeutic adjunct for children with Cerebral Palsy, warranting substantive confirmatory study. Gross Motor Function Measure, with modifications to improve sensitivity, appeared appropriate as a primary measure, with Timed up and Go test secondary. The intervention was inexpensive costing £20 per child. An explanatory trial to evaluate the clinical/cost-effectiveness of commercial system virtual reality therapy is feasible with minor methodological adaptation. Implications for rehabilitation: Home-based interactive computer gaming was feasible, safe and cost effective as a therapy adjunct. Discontinue if additional pressures are present: imminent surgery, family resilience to technical difficulties, negative system feedback, after-school activities. Change in Gross Motor Function Measurement scores varied by severity of Cerebral Palsy.